Study of the Wave - Convection - Rainfall interactions and impact of the Monsoon flux variability over the West Africa. - (:unkn) unknown (My University, 2006)
In the West Africa area and especially over the sahel, climate changing possess a great impact on the populationn where agricultural and breeding economies are exposed to drought threat. Therefore, the understanding of climate behavior and its variability, particulary the knowledge of atmospheric perturbations and theirs consequences on the rainfall dynamical processes are very important to define accomodate strategies. This thesis poit out rainfall variability due to atmospheric perturbations. The aims of this study are to understand how the perturbations in the 700 hPa wind field, the Africa Easterly Waves (AEWs) can modulate convective activity and rainfall, and the effects of these AEWs in the intra seasonal and interannal tie scales. The first part of this thesis describes the state of art of the West African climate. In the second part, the AEWs detection methodology, as well as its main characteristics are presented. In the third part, the inter annual variability of the rainfall is analysed by signal treatment method. The fourth part shows the interaction between AEWs convective activity and rainfall. The impact of AEWs sector exibits a great spatial variability. This study is extended by the local and large scale effects of AEWs. The low level conditions appear important to generate both convection and rainfall. In the last part, the intra seasonal variability of the Monsoon flux is analysed. The impact of AEWs and convection on these pulsations are shown.
Keywords: African Research